Tweeting through troubles: Exploring the connection between self-disclosure on the autobase Twitter account and emotion-focused coping strategies - Nugroho, Alnico Imam; Nurhayati, Siti Rohmah (Faculty of Psychology, Universitas Negeri Yogyakarta, 2023)
Social media Twitter, especially autobase @Jogjamnfs account should be used to inquire about things related to Yogyakarta. However, the followers of this account use it to do self-disclosure. In connection with that the sender cannot show his capability in managing this emotion that comes to the tweet that they send. Therefore, this research aims to find out the relations between self disclosure that is conducted through social media twitter on @Jogjamnfs account with senders' emotion focused coping. Participants of this research are 392 followers of @Jogjamnfs account. The method used in this research is a quantitative research method with correlational design. The sampling of this research used accidental sampling. The result of this research shows that there is a significant positive relationship between self disclosure and senders' emotion focused coping (p=0.000 and r=0.33). It means that if there is an increase of self disclosure than related to emotion focused coping increasing and vice versa. The followers of @Jogjamnfs account on average have self disclosure behavior at medium level with high emotion focused coping.